2019
DOI: 10.3389/fncel.2019.00452
|View full text |Cite
|
Sign up to set email alerts
|

Flexor and Extensor Ankle Afferents Broadly Innervate Locomotor Spinal Shox2 Neurons and Induce Similar Effects in Neonatal Mice

Abstract: Central pattern generators (CPGs) in the thoracolumbar spinal cord generate the basic hindlimb locomotor pattern. The locomotor CPG integrates descending commands and sensory information from the periphery to activate, modulate and halt the rhythmic program. General CPG function and response to sensory perturbations are well described in cat and rat models. In mouse, roles for many genetically identified spinal interneurons have been inferred from locomotor alterations following population deletion or modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…However it is not suitable for recording recurrent circuits, that are mostly located in the ventral horn. A dorsal horn ablated spinal cord preparation has already been described, and used in neonatal cords to record from V2a, Shox2, and Chx10 interneurons, as well as for fictive locomotion (Bhumbra & Beato, 2018; Dougherty & Kiehn, 2010; Li et al, 2019). Here we report that the dorsal horn-ablated preparation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However it is not suitable for recording recurrent circuits, that are mostly located in the ventral horn. A dorsal horn ablated spinal cord preparation has already been described, and used in neonatal cords to record from V2a, Shox2, and Chx10 interneurons, as well as for fictive locomotion (Bhumbra & Beato, 2018; Dougherty & Kiehn, 2010; Li et al, 2019). Here we report that the dorsal horn-ablated preparation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are a more limited number of research publications of more direct significance to our present work, and that include the cholinergic V0C interneurons (Zagoraiou et al, 2009), the Hb9 interneurons (Wilson et al 2005 andCaldeira et al 2017), and not least the Shox2 excitatory interneurons described by Dougherty et al (2013). Li et al (2019) have recently investigated whether a group of Shox2-nonV2a neurons (presumed rhythm-generating neurons; see Dougherty et al, 2013) also received short latency excitation from extensor gr I afferents in the neonatal mouse. The work by Li et al (2019) is still not conclusive with regard to the specific short-latency excitation from extensor gr I afferents, but certainly opens for the possibility of a successful analysis at the neonatal stage in the mouse.…”
Section: Figure 9 Near Herementioning
confidence: 99%
“…Li et al (2019) have recently investigated whether a group of Shox2-nonV2a neurons (presumed rhythm-generating neurons; see Dougherty et al, 2013) also received short latency excitation from extensor gr I afferents in the neonatal mouse. The work by Li et al (2019) is still not conclusive with regard to the specific short-latency excitation from extensor gr I afferents, but certainly opens for the possibility of a successful analysis at the neonatal stage in the mouse. It also provides a link between a large body of studies in the adult cat and the modern approaches investigating electrophysiology and anatomy of neurons expressing selective transcriptional factors identified and manipulated by genetic tools.…”
Section: Figure 9 Near Herementioning
confidence: 99%
“…ES uses sensory afferent fibers to access spinal locomotor circuitry in an attempt to facilitate motor function after SCI (10,16,32,33,(51)(52)(53)(54)(55). We previously showed that sensory afferent transmission to Shox2 interneurons is both excitatory and inhibitory in uninjured mice (25,56) but changes to mainly excitatory after chronic (>7 weeks) SCI (25).…”
Section: The Effects Of Sci and Es On The Sensory Afferent Transmissi...mentioning
confidence: 99%